1999
DOI: 10.1152/ajprenal.1999.276.2.f246
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of cytochromeP-450 4A1 and 4A2 to vascular 20-hydroxyeicosatetraenoic acid synthesis in rat kidneys

Abstract: 20-Hydroxyeicosatetraenoic acids (20-HETE), a biologically active cytochrome P-450 (CYP) metabolite of arachidonic acid in the rat kidney, can be catalyzed by CYP4A isoforms including CYP4A1, CYP4A2, and CYP4A3. To determine the contribution of CYP4A isoforms to renal 20-HETE synthesis, specific antisense oligonucleotides (ODNs) were developed, and their specificity was examined in vitro in Sf9 cells expressing CYP4A isoforms and in vivo in Sprague-Dawley rats. Administration of CYP4A2 antisense ODNs (167 nmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
96
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(98 citation statements)
references
References 28 publications
1
96
0
Order By: Relevance
“…CYP4A1 and CYP4A2 antisense oligonucleotides inhibit 20-HETE synthesis in both the vasculature and renal tubules and have an antihypertensive effect in Sprague-Dawley rats and SHRs (47,48). Antisense oligonucleotides have also been used to demonstrate that CYP4A1 plays an important role in mesenteric vascular reactivity (48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CYP4A1 and CYP4A2 antisense oligonucleotides inhibit 20-HETE synthesis in both the vasculature and renal tubules and have an antihypertensive effect in Sprague-Dawley rats and SHRs (47,48). Antisense oligonucleotides have also been used to demonstrate that CYP4A1 plays an important role in mesenteric vascular reactivity (48).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, mechanism-based CYP inhibitors and antisense oligonucleotides have been used to manipulate CYP eicosanoid production in vivo. Administration of CYP4A1 and CYP4A2 antisense oligonucleotides to SHR and Sprague-Dawley rats resulted in decreased levels of CYP4A mRNA and immunoreactive proteins and significant reduction of mean arterial blood pressure (MAP; 47,48). Studies in our laboratory demonstrated that 1-aminobenzotriazole (ABT) is a potent inhibitor of renal arachidonic acid -and ( -1)-hydroxylases with little effect on epoxygenases and that ABT has an antihypertensive effect in 7-wk-old SHRs (45).…”
mentioning
confidence: 98%
“…Furthermore, since the proximal tubule is where most electrolyte and water reabsorption occurs (1), the capacity of 20-HETE to potently inhibit Na ϩ /K ϩ -ATPase activity in this region of the nephron probably contributes to its known natriuretic and diuretic effects (4,62,74). In rats, CYP4A expression and 20-HETE formation have also been noted in renal microvessels (19,29,75), another proposed site where this eicosanoid influences vascular tone, autoregulation of renal blood flow, and/or tubuloglomerular feedback (9,10). However, the absence of CYP4 enzymes from the human renal vasculature suggests that synthesis of 20-HETE exclusively within the proximal tubules is sufficient for this compound to elicit its potent effects on kidney function.…”
Section: -Hete Formation By Human Renal P450 Enzymesmentioning
confidence: 99%
“…[2][3][4][5] The synthesis of 20-HETE is catalyzed primarily by enzymes of the cytochrome P450 (CYP) 4A family. 6,7 CYP4A proteins are present in vascular tissues and show distinct distribution along the vascular tree. 8 Suppression and overexpression of CYP4A proteins in small arteries and arterioles decreases and increases, respectively, vascular reactivity and myogenic tone 7,9,10 ; these effects can be reversed by the addition of 20-HETE or inhibition of its synthesis.…”
mentioning
confidence: 99%
“…In the spontaneously hypertensive rat, depletion or inhibition of CYP4A activity lowers blood pressure (BP). 11,12 Inhibition of vascular 20-HETE synthesis by intravenous administration of CYP4A1 or CYP4A2 antisense oligonucleotides decreases BP in normotensive and hypertensive rats, 6,7 whereas transduction with adenoviruses expressing the CYP4A2 protein increases vascular CYP4A expression and 20-HETE levels and augments BP. 13 A role for androgens in promoting elevation of BP is well recognized 14 and, according to recent studies, such a role may rely on increased synthesis of vascular 20-HETE.…”
mentioning
confidence: 99%